Dopamine β hydroxylase (DBH) polymorphisms do not contribute towards the clinical course of Wilson's disease in Indian patients. (23rd July 2019) - Roy, Shubhrajit; Ghosh, Sampurna; Bhattacharya, Sreyashi; Saha, Arpan; Das, Shyamal Kumar; Gangopadhyay, Prasanta Kumar; Bavdekar, Ashish; Ray, Kunal; Sengupta, Mainak; Ray, Jharna
Abstract: Background: Wilson's disease (WD) is a rare copper metabolism disorder with hepatic and neurological symptoms. Dopamine β hydroxylase ( DBH ) encodes a copper‐dependent mono‐oxygenase that converts dopamine to norepinephrine, thereby regulating the endogenous dopamine content in the neurons. Polymorphisms of DBH have been reported to be associated with several neurological diseases, such as Parkinson's disease, Alzheimer's disease, schizophrenia and attention‐deficit hyperactivity disorder, which have overlapping neurological symptoms with WD. The present study aimed to assess the role of DBH polymorphisms on the clinical course of WD. Methods: In total, 141 WD patients from India were included in the present study. Three polymorphisms of DBH (rs1611115 in the promoter, rs1108580 in exon 2 and rs129882 in 3'‐UTR) were screened for their association with the clinical attributes (hepatic and neurological features) and age of onset of WD using a polymerase chain reaction‐restriction fragment length polymorphsm method and sequencing approach. The distribution of genotype or allele frequencies was tested using 2 × 2 contingency chi‐squared and logistic regression analysis (additive, dominant and recessive model). Results: The genotypic and allelic frequencies of these single nucleotide polymophisms did not vary significantly along with the clinical symptoms (hepatic and neurological) or the age of onset of WD. No significant association was observed when we analyzed our samples with respect to harboring different kinds of ATP7B mutations (nonsense/in‐del and missense). Conclusions: The data obtained in the present study suggest that the selected DBH variants are unlikely to have any significant contribution towards modifying the clinical symptoms of Indian WD patients.